A consecutive, prospective analysis of the Rotoglide 1st metatarsophalangeal joint replacement. (June 2019) - Rajan, R.A.; Kodumuri, P.; Papamerkouriou, Y.; Kerr, M.; Evans, H.
Highlights: Following 1st metatarsophalangeal joint replacement, there is a normalisation of the distribution of the foot pedobarographic pressure. The kinematics as measured by detailed 3D motion analysis are maintained and there is an improvement in the patient reported outcome measure. Abstract: Following 1st metatarsophalangeal joint replacement, there is a normalisation of foot pressure distribution as demonstrated by peak pressures of the 1st and 5th metatarsal heads and their ratio as measured by pedobarographs. This compares favourably with the unaffected foot. Functional dorsiflexion range of motion is maintained and there is a significant improvement in the reported patient outcome measure.